Standarisasi Ekstrak Etanol Daun Ketepeng Cina (Cassia alata L.) yang Berasal dari Lingkungan Marusu Kelurahan Pallantikang Kabupaten Maros - Indah Astuti Pratiwi Paerah; marwah - (Jurnal Farmasi UIN Alauddin Makassar, 2021)
The community has used the Chinese Ketepeng Leaf (Cassia alata L.) as a traditional medicine for antiparasitic, treating ringworm, scabies, tinea versicolor, eczema, malaria, constipation, ulcerative skin inflammation, syphilis, herpes, influenza, bronchitis. The purpose of this study was to determine the specific and non-specific standards of the ethanol extract of the leaves of the Chinese Ketepeng (Cassia alata L.). The extract was obtained by maceration method using 96% ethanol. Specific parameters include organoleptic observations of viscous extracts, showing dark green color, characteristic odor, and bitter taste. Contains saponins, tannins, quinones, alkaloids. The content of compounds that are soluble in water is 24,0%, while the levels of compounds that are soluble in ethanol are 23.7%. The non-specific parameters of drying shrinkage were 8.98%, specific gravity of water was 0.987 g/ml, extract density at 5% dilution concentration was 1.012 g/ml, extract density at 8% dilution concentration was 1.023 g/ml, total ash content 14.4%, acid insoluble ash content 16.1%, total bacterial contamination 8 x 10-2, 6 x 10-3, 5 x 10-4 colonies and total mold contamination 2 x 10-1 colonies.